Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-04T10:56:11+01:00
2x-4(y+1)=10
2(x+3)-(1-y)=9

2x-4y-4=10
2x+6-1+y=9

2x-4y=10+4
2x+y=9-6+1

2x-4y=14
y=4-2x

2x-4(4-2x)=14
y=4-2x

2x-16+8x=14
y=4-2x

2x+8x=14+16
y=4-2x

10x=30/:10
y=4-2x

x=3
y=4-2*3

x=3
y=4-6

x=3
y=-2



1 5 1
2010-02-04T10:56:28+01:00
2x-4y-4=10
2x-4y=10+4
2x-4y=14
2x=14+4y :2
x=7+2y

2x+6-1+y=9
2x+5+y=9
2x=9-5-y
2x=4-y :2
x=2-½y
2010-02-04T11:49:30+01:00
2x-4y-4=10
2x+6-1+y=9

2x-4y=10+4
2x+y=9-5

2x-4y=14 /÷ (-1)
2x+y=4

2x+4y=-14
2x+y=4

-2x+4y+2x+y=-14+4
5y=-10 /÷5
y=-2

2x-2=4
2x=4+2
2x=6 /÷2
x=3

y=-2
x=3
1 5 1